Upper and Lower Bounds for the Kirchhoff Index of the n-Dimensional Hypercube Network. (16th June 2020) - Liu, Jia-Bao; Zhao, Jing; Shi, Zhi-Yu; Cao, Jinde; Alsaadi, Fuad E.
Abstract : The hypercube Q n is one of the most admirable and efficient interconnection network due to its excellent performance for some practical applications. The Kirchhoff index Kf G is equal to the sum of resistance distances between any pairs of vertices in networks. In this paper, we deduce some bounds with respect to Kirchhoff index of hypercube network Q n .